1999
DOI: 10.1080/03601239909373204
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and leaching of atrazine and alachlor on a sandy soil as affected by application in sprinkler irrigation

Abstract: Rainfall simulation was used with small packed boxes of soil to compare runoff of herbicides applied by conventional spray and injection into sprinkler-irrigation (chemigation), under severe rainfall conditions. It was hypothesized that the larger water volumes used in chemigation would leach some of the chemicals out of the soil surface rainfall interaction zone, and thus reduce the amounts of herbicides available for runoff. A 47-mm rain falling in a 2-hour event 24 hours after application of alachlor (2-chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Edwards et al (24) measured concentrations of atrazine and alachlor in the 2000-7000 µg/L range in pools formed in surface depressions in a corn field when simulated rainfall was applied on days 1, 2, 4, and 8 after application of the herbicides. Abdel-Rahman et al (25), with tilted beds of packed soil, measured in splash/ runoff from simulated rain concentrations of atrazine in excess of 70 000 µg/L and of alachlor exceeding 20 000 µg/L. These investigators concluded that an atrazine concentration in runoff twice its water solubility indicated the transfer of particulate material in the splash/runoff event.…”
Section: Resultsmentioning
confidence: 99%
“…Edwards et al (24) measured concentrations of atrazine and alachlor in the 2000-7000 µg/L range in pools formed in surface depressions in a corn field when simulated rainfall was applied on days 1, 2, 4, and 8 after application of the herbicides. Abdel-Rahman et al (25), with tilted beds of packed soil, measured in splash/ runoff from simulated rain concentrations of atrazine in excess of 70 000 µg/L and of alachlor exceeding 20 000 µg/L. These investigators concluded that an atrazine concentration in runoff twice its water solubility indicated the transfer of particulate material in the splash/runoff event.…”
Section: Resultsmentioning
confidence: 99%
“…The total losses, however, were less than 0.1% even in the broadcast method, which was applied at five times the banded application rate (1.7 kg a.i./ha versus 0.34 kg a.i./ha). Atrazine and alachlor losses in runoff were found to be reduced by 90% or more by applying the herbicides through chemigation as opposed to conventional broadcast spraying (Abdel-Rahman et al, 1999).…”
Section: Leaching Occurrence and Persistence Of Pollutants In Soil mentioning
confidence: 99%